Shoshana [videorecording (DVD)] - Winterbottom, Michael; Coriat, Laurence; Viragh, Paul; Booth, Douglas, 1992-; Starshenbaum, Irina, 1992-; Melling, Harry, 1989-; Alby, Aury; Seker, Ofer; Chris, Oliver, 1978-; Bramhill, Gina, 1989-; Hart, Ian, 1964-; Unwin, Anthony; et al. (Greenwich Entertainment, 2025)
"In this edge-of-your-seat thriller inspired by real events, a British police officer and a Jewish woman fall in love amidst the political turmoil of 1930s Tel Aviv. With British control over Palestine precarious and conflict inevitable, everyone is forced to choose a side."--